ANALISIS PENOKOHAN DALAM NOVEL ANAKKU DIPOTRET MALAIKAT KARYA ADNAN KATINO - Priyadi, Totok; Wartiningsih, Agus; Na’im, Nur Arifin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstrak: Penelitian ini bertujuan mengetahui pengklasifikasian tokoh dan penokohan dalam novel ADM karya Adnan Katino. Metode penelitian yang digunakan adalah deskriptif. Hasil analisis tokoh yaitu pertama, Nasib digolongkan tokoh utama, protagonis, dan netral. Kedua, Asih digolongkan tokoh antagonis, kompleks, dan netral. Ketiga, Mamat digolongkan tokoh tambahan, antagonis, dan kompleks. Keempat, Supriono digolongkan tokoh protagonis dan tipikal. Kelima, Denok digolongkan tokoh datar dan netral.  Keenam, Roy Ceking digolongkan tokoh tambahan dan antagonis. Ketujuh, Penyok digolongkan tokoh datar, tambahan, dan protagonis. Kedelapan, Basyir digolongkan tokoh tambahan dan protagonis. Kesembilan, Babe digolongkan tokoh tambahan, antagonis, dan kompleks.  Kesepuluh, Pak Giok digolongkan tokoh protagonis, kompleks, dan tipikal. Kesebelas, Buya, digolongkan tokoh netral. Penokohan dalam novel ADM yaitu Nasib ditampilkan secara campuran, Mamat secara dramatik, Asih secara campuran, Supriono  secara campuran,  Denok secara dramatik, Penyok secara campuran, Buya secara dramatik, Babe secara dramatik, Roy Ceking secara dramatik, Pak Giok secara dramatik, dan Basyir ditampilkan secara dramatik.   Kata kunci: Tokoh, Penokohan, Novel, Struktural Abstrack: This study aims to determine the classification of the characters and characterizations in the novel ADM by Adnan Katino. The method used is descriptive. The results of the analysis of the characters and characterizations contained in the novel ADM firstly by Adnan Katino, the results of the analysis of figures and characters in the novel ADM firstly, Nasib are classified into main character, protagonist, simple, and neutral. Secondly, Asih is classified into additional, antagonist, complex, and neutral. Then, Mamat classified into additional figures, additional, antagonists, and complex. Fourth, Supriono is classified into additional, simple, protagonist, and typical. Then, Denok, classified into additional, protagonist, simple, and flatand neutral character. The sixth, Roy Ceking is classified into additional, antagonistic and an extra character. Next, Penyok is classified into additional, simple, and the protagonist. Then, Basyir classed into the additional characters, protagonists and complex . Then, Babe is classified into the additional characters, antagonists, and complex. Next, Pak Giok classified into the additional characters, protagonist, complex, and typical. The last, Buya is classified into the additional characters, protagonist, additional, and  neutral. Characters featured in the novel ADM classified in two ways, namely, dramatic (indirect), and mix. The character of Mamat discribed dramatically, Denok dramatically, and Roy Ceking dramatically, and Basyir dramatically, and Babe dramatically, and Pak Giok dramatically, and Penyok dramatically, and Asih mix, and Nasib mix, and Supriono mix,  and Buya mix. Keywords: Characters, Characterizations, Novel, Structural